The Utilisation of Migrant Capital to Access the Labour Market: The Case of Swedish Migrants in Helsinki - Östen Wahlbeck; Sabina Fortelius (Social Inclusion, 2019)
This article explains from a Bourdieusian perspective how migrants gain access to fields in which their resources are valued and their cultural and social capital can be mobilised. Interviews conducted among Swedish migrants in Helsinki (Helsingfors) illustrate how the migrants have been able to utilise various forms of capital to gain access to the local labour market. Knowledge of the Swedish language and society may constitute cultural capital, but only in specific occupations and social contexts. The article highlights the importance of access to social networks among Finnish spouses and friends in finding information about the jobs in which knowledge of the Swedish language and society is valued. The results indicate that the resources of migrants do not always constitute a valuable social capital, migrants also need to be able to mobilise their resources in a given social context. It is also argued that there may be specific forms of cultural and social capital that are only available to migrants as a consequence of their being migrants. This migrant capital consists of the various forms of capital that are connected to the migration process and are mobilisable by the migrants.